Conceptualizing “Vulnerability” in the European Legal Space: Mixed Migration Flows and Human Trafficking as a Test - De Stefani, Paolo (Frontiers in Human Dynamics, 2022)
The article discusses the role of “vulnerability” in the legal and political discourse of today's Europe as a dual-mode dispositive. On the one hand, “vulnerability” allows the legal formalism to incorporate the precarious subjects that the traditional language of “rights” risks to exclude. Compared with the human rights language, “vulnerability” better articulates the relationship between legal categories and rapidly changing social and ecological landscapes. The “vulnerability language” captures intersectionality. On the other hand, however, through examples taken from the EU normative production on irregular and mixed migrations, with a focus on refugee “screening” and reception and on managing identification and referral procedures of persons victims of human trafficking, this article shows that the assignment of an individual to a “vulnerable group” has the effect not only of expanding and intensifying their protection under normative human rights regimes, but also of accentuating some risks already inherent in human rights discourse, namely paternalism and essentialism. Paradoxically, a possible outcome can be fragmentation of rights protection frameworks, and exclusion. Vulnerable migrants may have to face additional challenges stemming from their inability (coupled with objective difficulty) to decodify communications and instructions concerning their status. Divergent ways of conceiving vulnerability, depending on subjective assessments, public policy standards, the legal framework, and the political agenda on welfare, contribute to neutralizing the potentially emancipatory impact of the vulnerability language.